(untitled) (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: This study aimed to investigate the metagenomic and microbial diversity of dadih in Kampar District, Riau, Indonesia. Materials and Methods: The dadih samples were collected from dadih producers in three villages, namely Limau Manis(LM), Rumbio (RB), and Muaro Jalai (MJ). DNA samples were extracted and sequenced through Oxford Nanopore Technology (ONT), operated by MinKNOW software version 23.04.5. Library preparations were conducted using kits from ONT. Results: The next-generation sequencing analysis on three dadih from Kampar identified two bacterial phyla, Bacillota and Pseudomonadota. Furthermore, there was a slight variation in dadih’s microbiota composition between LM, RB, and MJ. The Bacillota phylum dominated the dadih microbiota in LM and RB villages, with a relative abundance of 60%–80%. The dadih from MJ was dominated by the phylum Pseudomonadota, which reached 55%. The dominant species found in all three dadih was Lactococcus lactis, with an abundance of 53.80, 80.80, and 40.31% for dadih LM, RB, and MJ, respectively. Conclusion: Dadih MJ had the highest Simpson’s value ( 0.8), showing a relatively even abundance of species in the sample. Furthermore, dadih LM had a high Simpson’s value ( 0.75), indicating similar conditions to dadih MJ. Dadih RB had the lowest Simpson’s value ( 0.4), confirming that the microbiota in the sample tends to be dominated by certain species with a less even distribution. J. Adv. Vet. Anim. Res., 12(3): 717–727, September 2025 http://doi.org/10.5455/javar.2025.l935